Kajian Morfisme Untuk Variasi Kurva Dense Fibonacci Word - Anggi Enggar Sari; Kosala Dwidja Purnomo; Firdaus Ubaidillah (Jurnal Matematika, 2021)
The Fibonacci word is one example of a fractal object. The fractal Fibonacci word has the property of being similar to curves with curves. The curve Fibonacci word generated based on the Fibonacci word sequence. The Fibonacci word sequence can be defined by morphism so that a new sequence with the three-digit rule {0,1,2} is called Dense Fibonacci Word. In this research, the variation of the curve Dense Fibonacci Word generated by using the method L-Systems which applies several morphisms. This research method is divided into five stages, the first is the interpretation of the Dense Fibonacci Word and variations of morphism based on the Fibonacci word sequence. Second, the interpretation of fractals Dense Fibonacci Word using the method L-Systems mathematically. Third, the interpretation of fractals Dense Fibonacci Word using the method L-Systems graphically. Fourth, program making and fifth, analysis of results. The results obtained in this study are the visualization of the curve Dense Fibonacci Word with the method L-Systems, the shape of the curve Dense Fibonacci Word varies by applying several morphisms. The variation of the curve Dense Fibonacci Word is compared to each morphism which results in a different shape of the curve Dense Fibonacci Word in the small generation, but the larger the generation the fractal pattern is the same.